060 Fulminant meningitis as a presenting feature of anti-NMDA receptor encephalitis. Issue 12 (14th November 2019) - Stavrou, Maria; Yeo, Jing Ming; Slater, Alexander David; Irani, Sarosh; Foley, Peter
Abstract : Anti-NMDA receptor encephalitis is a well-recognised immunotherapy-responsive condition which often occurs as a paraneoplastic phenomenon. A typical presentation is in a young individual with a viral-like prodrome followed by the development of severe psychiatric symptoms, memory loss, seizures, reduced consciousness and sometimes orofacial dyskinesias, and progression to autonomic and respiratory instability. Fulminant meningitis is a very rare presenting feature of anti-NMDA receptor encephalitis with our literature search only revealing one other reported case. We present a case of a 33-year old Caucasian woman who initially presented with lymphocytic meningitis but subsequently developed clinical and investigative features consistent with anti-NMDA receptor encephalitis. Through this case, we aim to present and discuss possible mechanisms 1–3 underlying this atypical presentation and to highlight frank meningitis as an atypical presenting feature of anti-NMDA-receptor encephalitis. Clinicians should consider autoimmune encephalitides in individuals with meningitis, particularly where extensive investigations fail to identify a causative micro-organism and there is rapid development of an encephalitic phenotype. A multidisciplinary approach is required to address the neurological, gynaecological, oncological, and neuropsychiatric aspects of this challenging and incompletely understood disorder. References: Bektaş Ö, et al. Neuropediatrics 2014;45(6):396–401 Irani SR, et al. Brain 2010;133(Pt 6):1655–67 Dalmau J, et al. Lancet Neurol 2008;7(12):1091–8